HbA1c: an independent risk factor for dysthyroid optic neuropathy - Wang, Xing; Ye, Huijing; Chen, Rongxin; Yang, Shenglan; Zhang, Te; Xiao, Wei; Yang, Huasheng (Frontiers in Endocrinology, 2023)
Background We aimed to explore the frequencies of islet β-cell autoantibodies and insulin resistance (IR) in thyroid-associated ophthalmopathy (TAO) and identify specific diabetes mellitus (DM) indicators as early predictors for dysthyroid optic neuropathy (DON). Methods Ninety-eight TAO patients (57 DON and 41 non-DON patients) and 48 healthy control (HC) participants were recruited for this prospective cross-sectional study. Serum thyroxine, serum thyroid autoantibodies, serum humoral immune markers against islet β-cell, fasting plasma glucose (FPG), fasting serum insulin (FINS), fasting c-peptide (FCP), and glycosylated hemoglobin A1 (HbA1c) were measured. Logistic regression analysis was used to evaluate the correlation of patients’ age, body mass index (BMI), FPG, HbA1c, and related indexes of islet β-cell function to the occurrence of DON. Results The DON group had higher FPG (P<0.001, 0.016) and HbA1c (P<0.0001, P<0.001) levels than the HC and non-DON groups. The homeostasis model assessment (HOMA)-IR level was the highest in the DON group (HC 2.15 ± 0.89, non-DON 2.41 ± 1.24, and DON 2.82 ± 2.65), while the HOMA-β level was the lowest (HC 101.8 ± 44.75%, non-DON 102.9 ± 54.61%, and DON 88.29 ± 52.75%), with no significant differences (P=1, P>0.05). On univariate analysis, age (P=0.006), BMI (P=0.022), history of steroid use (P=0.014), FPG (P=0.013), and HbA1c (P=0.001) levels were significantly associated with the presence/absence of DON. In addition, after adjusting for potential confounds, the HbA1c level was an independent factor associated with DON (P=0.009, OR=4.012). Conclusions HbA1c is an independent risk factor for DON. Given the interconnected link between thyroid dysfunction and DM, the use of HbA1c as a potential biomarker for DON warrants further investigation.